MEMBANGUN JEMBATAN KERUKUNAN ANTARAGAMA MELALUI PENDIDIKAN AGAMA KRISTEN - Tangkuman, Fabian H. R. S; Komaling, Olga N; Kambey, Vincen R. (STT KINGDOM BALI, 2026)
This study examines the role of Christian Religious Education (PAK) in building interfaith harmony in Indonesia's diverse society. Interfaith harmony is understood as a state of harmony characterized by mutual respect and the ability to live side by side peacefully. PAK plays a significant role in instilling the values of love, tolerance, and respect for differences through dialogical learning based on Christian character. This study highlights the importance of integrating harmony values into the curriculum, enhancing students' understanding of other religions, and the role of teachers as role models and facilitators of peace. The results indicate that implementing appropriate PAK strategies can strengthen a culture of peace and encourage more constructive interfaith relations. This study recommends strengthening educator competencies, developing an inclusive curriculum, and enhancing interfaith cooperation as sustainable steps in building interfaith harmony.